Projeto de abrigo emergencial desmontável composto por peças pré-fabricadas leves e autoportantes em bambu e bioconcreto - Lima, Carla Magalhães (2020)
Bamboo is used as a construction system in different types of buildings. Its application in emergency shelters, which play a vital role in scenarios of politicalreligious persecution or homelessness, provides lightness and aesthetics. However, if added to a bioconcrete closure, it acquires relevant features such as environmental comfort, easy transport and assembly. These materials are a more ecological alternative compared to those traditionally applied in emergency shelters. For this purpose, this work proposes a prefabricated modular construction system composed of pieces with a structure in stems of Mossô bamboo and a fence in bamboo bioconcrete. The culms of the prefabricated piece, its fish-mouth fitting, its connections and its bioconcrete were experimentally characterized. The bioconcrete studied with 45% of bamboo residues by volume showed mechanical results of resistance to compression and flexion of 8.11 MPa and 2.69 MPa, respectively. The compressive strength tests of the bamboo beam-stalk system pointed out that the beam diaphragm positioned on the pillar axis with a fish mouth is the best configuration for this type of orthogonal fitting. The modular structure designed with the construction system was analyzed using SAP 2000 software, obtaining satisfactory results for use in emergency shelters in different locations in Brazil